Inequality and the time structure of earnings: Evidence from Germany - Carsten Schröder; Yolanda Golan; Shlomo Yitzhaki (Journal of Economic Inequality, 2014)
This paper studies the relationships between annual and subannual inequality and mobility during the course of the year. We apply an exact decomposition framework as outlined in Wodon and Yitzhaki (Econ Bull 4:1–8, 2003), and in Yitzhaki and Wodon (Research on Economic Inequality 12:179–199, 2004). Earnings records of pension insurants in Germany serve as the database. The long time horizon of our database allows us to investigate the stability and robustness of the parameters of the decomposition over time. Specifically, we show that the mobility component of the decomposition, as measured by Gini correlation coefficients, changes over the observation period. This makes it difficult to predict the impact of the income accounting period on inequality in a more general context. Thus, it is of paramount importance to use income data from a uniform accounting period in distributional analyses.
Additional information: The final publication is available at www.springerlink.com: http://dx.doi.org/10.1007/s10888-013-9260-9
Keywords: 330; Accounting period; Time structure of earnings; Gini decomposition; Inequality; Mobility; Re-ranking; Einkommensverteilung; Lebenseinkommen; Deutschland